The Influence of Self-Concept on Career Decision-Making Ability among Grade XI Students at SMAN 2 Bogor City - Nuzulia Rahma; Reni Sinta Dewi; Noneng Siti Rosidah (al-Afkar, Journal For Islamic Studies, 2026)
Career decision-making is an essential aspect of adolescent life. For some individuals, choosing a career is a journey of self-discovery, while for others, it becomes a challenge due to limited information or external pressures such as parental expectations, social norms, and peer influence. Therefore, adolescents need to have a good understanding of themselves, including their interests, abilities, and self-concept, to make appropriate career choices. This study aims to determine the influence of self-concept on the career decision-making ability of 11th-grade students at SMA Negeri 2 Bogor. The research employed a quantitative approach with a simple linear regression method. Data collection techniques included questionnaires and observation, while data analysis consisted of descriptive analysis, normality testing, homogeneity testing, and simple linear regression. The study population consisted of 333 students, with a sample of 189 students selected using the Slovin formula and random sampling technique. The results showed that students’ self-concept was categorized as moderate (67.7%), as was their career decision-making ability (69.8%). The regression analysis yielded a significance value of 0.000 (sig < 0.05), indicating a significant influence between self-concept and career decision-making ability. The contribution of self-concept to career decision-making ability was 54.9%, while the remaining 45.1% was influenced by other factors not examined in this study.